2019
DOI: 10.3390/ijerph16162964
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Through Barriers and Building Disaster Mental Resilience: A Case Study in the Aftermath of the 2015 Nepal Earthquakes

Abstract: Introduction: Nepal was hit by two devastating earthquakes in 2015 that disrupted its socio-economic system and shattered many lives, resulting in increased mental health issues during the post-earthquake phase. Disasters can have severe mental health impacts on the affected population, making it necessary to enhance resilience within communities and to help them to adapt well in the face of adversities. From these earthquakes, this study looks to identify measures needed to develop community mental resilience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 72 publications
2
13
0
1
Order By: Relevance
“…A recent study on preparedness for earthquakes in Nepal indicated that communities in the developing world demonstrate high resilience, to some extent, through the culture of sharing and helping each other. 11 Similarly, a secure community support system, also known as "ultrasociality," is deeply rooted in the social cohesion arising out of unified spiritual and religious beliefs in the Indian subcontinent. 12 This could be another contributor to better mental preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on preparedness for earthquakes in Nepal indicated that communities in the developing world demonstrate high resilience, to some extent, through the culture of sharing and helping each other. 11 Similarly, a secure community support system, also known as "ultrasociality," is deeply rooted in the social cohesion arising out of unified spiritual and religious beliefs in the Indian subcontinent. 12 This could be another contributor to better mental preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…The literature confirmed the relationship between collective efficacy and social exchange, which cultivated the capacity of the community members to prepare for and recover from disaster events [135]. Another study from a different setting also demonstrated that social cohesion is essential to speeding up the recovery process within the affected communities after two major earthquakes (magnitude 7.8 and 7.6) hit Nepal in 2015 [136].…”
Section: Discussion and Recommendations: The Way Forwardmentioning
confidence: 85%
“…Researchers have arrived at a consensus that governmental departments should be committed to organizing PFA (Kc et al, 2019). Our review revealed that both governmental and nongovernmental organizations are involved, which will have both advantages and disadvantages, depending on the political and civic society situation.…”
Section: Discussionmentioning
confidence: 99%
“…Contextualization is the incorporation of contextual details in practice, giving due consideration to the economic, cultural, political, and multifaceted aspects of a situation (Salet & de Vries, 2019). The optimal goal of PFA is to facilitate resilience, which is closely related to the local organizational, cultural, and societal background (Hechanova, Ramos, & Waelde, 2015; Kc, Gan, & Dwirahmadi, 2019). Some studies have reported the application of PFA in different disaster scenarios, but little is known about the application of PFA in the contexts of different disasters, cultures, political systems, and timing (Shultz & Forbes, 2014).…”
mentioning
confidence: 99%